CLOVIBACTIN : STUDI LITERATUR ANTIBIOTIK BARU YANG DIHARAPKAN DAPAT MENGATASI RESISTENSI - Wulida Nuril Fajriyah; Zamrotul Izzah; Eko Budi Koendhori; Afifah Listiadewi; Melisa Nur Diniah (Fakultas Farmasi Universitas Setia Budi, 2025)
This review discusses about that Clovibactin is a new antibiotic isolated from soil samples in the state of North Carolina. Clovibactin contains eight depsipeptide residues consisting of a macrolactone ring and a linear tail. This antibiotic is active against gram-positive bacteria, including drug-resistant human pathogens such as Methicillin-resistant Staphylococcus aureus, Vancomycin-resistant enterococci, dan Mycobacterium.tuberculosis. This review aims to assess the activity of clovibactin against Mycobacterium tuberculosis. Clovibactin works by inhibiting all cell wall biosynthesis reactions that consume lipid I, lipid II, lipid IIIwall teichoic acid or undecaprenyl-pyrophosphate (C55PP). Clovibactin showed no cytotoxicity to National Institute of Health/3T3 and HepG2 cells in mammals at a dose of 100 µg/mL. Clovibactin has bactericidal properties on gram-positive bacteria. Clovibactin has an MIC of 0.5-1 µg/mL on M.tuberculosis so it has good bactericidal efficacy with low toxicity.